Pengaruh Metode Pembelajaran E-Learning untuk Meningkatkan Motivasi Belajar Siswa - Althof, Jihan; Arba’iyah, Arba’iyah; Tantri, Kikan Sandiyus; Adam, Moh. Ibnu (Lembaga Yasin AlSys, 2023)
Lately there is a learning method that is often used when carrying out the process learning, namely the learning method of e-learning. This learning method is a method learning by implementing electronic digital learning systems that can be accessed anywhere at any time you want it. Therefore there is an e-learning learning method that combines learning with technology that has been highly developed in this generation and we as the next generation must be able to take advantage of existing technology as best as possible. This change in learning methods has various impacts negative impact on users such as educators and students who have a tendency not to understand what is being taught, lack of learning about technology to be used and so on. As for all that we should be able to take advantage of technology that has been created in such a way as possible. So that's the main goal of this e-learning learning method is actually used to increase student learning motivation in order to have a new atmosphere in the learning process so that students can develop deeper and wider knowledge.